2017
DOI: 10.1016/j.jclepro.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of green concretes for structural use

Abstract: This paper presents a comparative environmental assessment of several different green concrete mixes for structural use. Four green concrete mixes were compared with a conventional concrete mix: recycled aggregate concrete with a cement binder, high-volume fly ash concrete with natural and recycled aggregates, and alkali activated fly ash concrete with natural aggregates. All five concrete mixes were designed and experimentally verified to have equal compressive strength and workability. An attributional life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(77 citation statements)
references
References 71 publications
1
73
0
3
Order By: Relevance
“…An interesting study was proposed by [44] in which green concrete mixes were compared with a conventional concrete mix. The final results highlighted that RCA with fly ash (FA) was the most suitable mixture.…”
Section: State Of Art Of Lca and Recycled Aggregates Concretementioning
confidence: 99%
“…An interesting study was proposed by [44] in which green concrete mixes were compared with a conventional concrete mix. The final results highlighted that RCA with fly ash (FA) was the most suitable mixture.…”
Section: State Of Art Of Lca and Recycled Aggregates Concretementioning
confidence: 99%
“…LCA studies have reported varying CFI of 320-343 kgCO 2 -eq/m 3 for 100% RCA concrete (Marinković et al 2017) and 271 kgCO 2 -eq/m 3 for 30% RCA concrete (Kleijer et al 2017). From this study, the CFI for 100% RCA OPC concrete in the Australian context is higher (516 kgCO 2 -eq/ m 3 ) as it includes emissions from upstream processes (Fig.…”
Section: Recycled Concrete Aggregate In Opc and Gpcmentioning
confidence: 68%
“…There have been many studies published that have compared the environmental impacts of RAC and NAC for structural use [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. The environmental impacts of concrete structural elements can be assessed, for instance, by the life cycle assessment method (LCA) [63].…”
Section: Introductionmentioning
confidence: 99%